Akcja Tilea. Rząd Rzeczypospolitej Polskiej na wychodźstwie i Rumuński Komitet Narodowy w Londynie - Bruski, Jan Jacek (1969– ) (Instytut Historii PAN, 2025)
The article examines the fate of the Roumanian National Committee, which was established in London in late 1940 at the initiative of Viorel Virgil Tilea. This organisation became the nucleus of the Free Roumanian Movement, which brought together various groups opposed to the regime of Marshal Ion Antonescu. Tilea's activities were blocked by the British in 1941, but the Committee still managed to gain the support of the Polish government-in-exile, which was pursuing broader plans related to the Continental Action. The article presents the showdown that took place between 1940 and 1942, involving the British authorities, the Romanian émigrés, and the Polish and Czechoslovak governments in exile.
p. 173-191
Summary in English.
Keywords: Roumanian National Committee; Tilea, Viorel Virgil, 1896-1972; Continental Action; Polish government in exile; British foreign policy; Special Operations Executiv; Great Britain.Army. Special Operations Executive.; Romania - relations - Great Britain - 1900-1945; Great Britain - relations - Romania - 1900-1945